Co-Intelligence: Living and Working with AI - Mollick, Ethan (WH Allen, 2024)
**A New York Times Bestseller**'Co-Intelligence is the very best book I know about the ins, outs, and ethics of generative AI. Drop everythi ng and read it cover to cover NOW' Angela DuckworthConsumer AI has arr ived. And with it, inescapable upheaval as we grapple with what it mea ns for our jobs, lives and the future of humanity.Cutting through the noise of AI evangelists and AI doom-mongers, Wharton professor Ethan M ollick has become one of the most prominent and provocative explainers of AI, focusing on the practical aspects of how these new tools for t hought can transform our world. In Co-Intelligence, he urges us to eng age with AI as co-worker, co-teacher and coach. Wide ranging, hugely t hought-provoking and optimistic, Co-Intelligence reveals the promise a nd power of this new era.